STRATEGI RUMAH SAKIT UMUM SWASTA DI PURWOKERTO DALAM MENGHADAPI AKREDITASI - Eka Noviati, Bernadetta (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Accreditation is an obligation that must be done by every hospital in Indonesia. Purwokerto is the capital of Banyumas district, Central Java, Indonesia. Health services in Purwokerto are facilitated by 10 Public Hospitals and 7 are private public hospitals. Based on the preliminary study, of the seven general hospitals, get one hospital that has been accredited. How is the strategy of public private hospitals facing accreditation, becoming an interesting topic to learn. Objective: The purpose of this research is private hospital strategy in Purwokerto to face hospital accreditation. Methods: The research method used is qualitative with phenomenology approach. Analysis the data research by using IPA (Interpretative Phenomenological Analysis). Results: Based on the analysis of 5 informants, the theme of accreditation strategy for private hospitals that are human resources control, owner and management commitment, programmatic procedures, time management, process strategy, and building a comfortable working environment. Conclutions: To be able of accreditation of public private hospitals need the ability to build human resources, and other resources both physical, facilities, environment and time management. Further research is expected to be implemented in all hospitals whether public hospitals, specialty, or clinics. Keywords: Accreditation, hospital, strategy